2017
DOI: 10.1002/hed.25017
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator activated receptor‐gamma stimulation for prevention of 5‐fluorouracil‐induced oral mucositis in mice

Abstract: The RGZ had a protective effect on oral mucosa damaged by chemotherapy. These data encourage the further study of RGZ for the prevention of 5-FU-induced mucositis in patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…PPARγ is a nuclear receptor that may be considered as an "atypical transcription factor" able to activate anti-inflammatory signals. Indeed, pharmacological stimulation of PPARγ exerts beneficial activity in oral mucositis [13,14]. In agreement with these findings we also investigated PPARγ and its co-activator PGC-1α and we found that the expression of this intracellular signal was "downregulated" in our model of oral mucositis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…PPARγ is a nuclear receptor that may be considered as an "atypical transcription factor" able to activate anti-inflammatory signals. Indeed, pharmacological stimulation of PPARγ exerts beneficial activity in oral mucositis [13,14]. In agreement with these findings we also investigated PPARγ and its co-activator PGC-1α and we found that the expression of this intracellular signal was "downregulated" in our model of oral mucositis.…”
Section: Discussionsupporting
confidence: 85%
“…In fact, ROS boosts the translocation to the nucleus of Nuclear Factor Kappa B (NF-κB) [12]. Once it reaches the nucleus, the transcription factor turns on genes that codify for inflammatory cytokines such as Tumor Necrosis Factor (TNF-α), Interleukin 1 beta (IL-1β) and IL-6; moreover at the same time, it silences genes priming anti-inflammatory signals, in particular IL-13 and the nuclear receptor called peroxisome proliferator-activated receptor gamma (PPAR-γ) [13,14]. Indeed, this NF-κB primed cytokine storm may be considered an important arm of the acute phase response, but it has also been reported to have a key role in driving the second wave of the acute response in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…RGZ is an intracellular ligand for PPAR-γ transcription factor that exerts antioxidant and anti-inflammatory activities. Currently, RGZ is used to control hyperglycemia in type II diabetes mellitus [ 55 , 56 ]. Additionally, it has been reported that the thiazolidinedione family of PPARγ agonists, including troglitazone (TGZ), pioglitazone (PGZ) and RGZ, have antitumor effects [ 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the ways that PPARs regulate inflammation is through a transrepression mechanism, where other transcription-factor, such as NF-κβ, is repressed to activate the expression of pro-inflammatory cytokines [ 55 ]. Consistent with the RGZ effects, Sottili and collaborators (2017) tested RGZ in a 5-FU-induced OM in mouse models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation